Organizational culture among levels of health care services in Crete (Greece) - Rovithis, Michael; Linardakis, Manolis; Merkouris, Anastasios; Patiraki, Elisabeth; Vassilaki, Maria; Philalithis, Anastas (My University, 2017)
As a concept, organizational culture is multifaceted and it has been studied in fields ranging from social anthropology to industrial-organizational psychology (Schein, 2010) defined as the set of beliefs, values, behavioral patterns, and assumptions shared by members of an organization (Cooke & Rousseau, 1998; Jacobs & Roodt, 2008; Scott, Mannion, Huw, & Marshall, 2003).Researchers in a variety of academic and professional disciplines have studied organizational culture and its possible impact on performance within organizations' services (Brian, Stanley, Armenakis, & Shook, 2009; Davies, Mannion, Jacobs, Powell, & Marshall, 2007; Freund & Drach-Zahavy, 2007; Xenikou & Simosi, 2006; Zheng, Baiyin, & McLean, 2010).
Keywords: Health care; Crete; Researched organizational surveys